From Home To The Environment: The Family’s Role In Optimizing Early Childhood Naturalistic Intelligence - Faridy, Faizatul; Sofyan Sufri (Bansigom Na Publisher, 2026)
This study aims to analyze the family's role in optimizing early childhood naturalistic intelligence through home-based to neighborhood ecological experiences. While the importance of the family in early environmental exposure is recognized, a gap exists in understanding how informal daily practices can be systematically leveraged to foster deeper ecological awareness. Employing a descriptive qualitative method, this research was conducted with 9 farming families in Peunalom II Village, Tangse-Pidie (Aceh), selected through purposive sampling. Data were gathered via semi-structured interviews, observation, and documentation, and analyzed through reduction, presentation, and verification. The key findings reveal that while families naturally serve as the primary center for stimulating naturalistic intelligence through spontaneous activities (e.g., interacting with animals, gardening, maintaining cleanliness), this stimulation remains predominantly practical. It lacks deliberate guidance toward conceptual understanding of the cause-effect relationship between human behavior and its environmental impact, thus limiting the optimal development of children's ecological consciousness. The study's main contribution lies in identifying this critical gap and, consequently, explicitly proposing a novel, structured family mentoring model based on the